Role of the Listeria monocytogenes 2‐Cys peroxiredoxin homologue in protection against oxidative and nitrosative stress and in virulence. Issue 1 (12th September 2013) - Dons, Lone E.; Mosa, Ahmed; Rottenberg, Martin E.; Rosenkrantz, Jesper T.; Kristensson, Krister; Olsen, John E.
Abstract: Peroxiredoxins contribute to protection of some bacteria against reactive oxygen intermediates (ROIs) and reactive nitrogen intermediates (RNIs). Listeria monocytogenes, a facultative intracellular bacterial pathogen, interacts with ROIs and RNIs during infection. In this study, we investigated the involvement of the 2‐Cys peroxiredoxin (Prx) homologue in L. monocytogenes in the protection against ROIs and RNIs and in virulence through the construction of an in‐frame prx deletion mutant. The Δ prx mutant had increased sensitivity to hydrogen peroxide and cumene hydroperoxide compared to the wild‐type strain. The mutant also exhibited an increased susceptibility to the nitric oxide‐generating compound S‐nitroso‐N‐acetylpenicillamine (SNAP) and 3‐morpholinosydnonimine hydrochloride (SIN‐1), a peroxynitrite donor. Furthermore, a diminished virulence of the Δ prx mutant relative to the wild‐type was observed in C57BL/6 mice, but not in inducible nitric oxide synthase‐deficient mice. The results suggest that Prx protects L. monocytogenes against oxidative and nitrosative stress in vitro and in vivo and that the prx ‐encoded polypeptide thereby is involved in L. monocytogenes virulence. Abstract : In this article the authors studied the role of a 2‐Cys peroxiredoxin (Prx) homologue in Listeria monocytogenes, an intracellular bacterial pathogen. They found that Prx contributes to resistance against reactive oxygen and nitrogen intermediates, and also to virulence in wild type mice but not in iNOS‐deficient mice, demonstrating the importance of this factor.